Research of the phenomenon of professional burnout of employees of the socio-pedagogical sphere (Educational Dimension, 2021)
The article presents a study of the phenomenon of burnout of employees of the socio-pedagogical sphere. The analysis of scientific sources allowed to generalize the concept of "professional burnout" as a state of emotional, physical and mental exhaustion caused by excessive and prolonged stress. At the same time, the factors influencing the occurrence of burnout are identified: lack of control, unclear expectations from work, lack of social support, imbalance between work and life, psycho-emotional instability. It is noted that the typical signs of psycho-emotional burnout are insomnia, insomnia, negative attitude towards colleagues, students, work, abuse of chemicals, lack of appetite or overeating, anxiety, irritability, tension, anger, resentment, general depression, guilt, loss of motivation and responsibility.